2018
DOI: 10.1111/imcb.12169
|View full text |Cite
|
Sign up to set email alerts
|

CD57 identifies T cells with functional senescence before terminal differentiation and relative telomere shortening in patients with activated PI3 kinase delta syndrome

Abstract: Premature T-cell immunosenescence with CD57 CD8 T-cell accumulation has been linked to immunodeficiency and autoimmunity in primary immunodeficiencies including activated PI3 kinase delta syndrome (APDS). To address whether CD57 marks the typical senescent T-cell population seen in adult individuals or identifies a distinct population in APDS, we compared CD57 CD8 T cells from mostly pediatric APDS patients to those of healthy adults with similarly prominent senescent T cells. CD57 CD8 T cells from APDS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Both patients in our study had short telomeres, consistent with previous reports 11,24,34 . Because the telomere length is highly variable according to race, age, and disease state, the cell surface marker CD57 is routinely used to identify terminally differentiated, senescent cells with reduced proliferative capacity and altered functional properties 22 . The expression of CD57 was dramatically elevated in CD4 and CD8 T cells in both patients in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both patients in our study had short telomeres, consistent with previous reports 11,24,34 . Because the telomere length is highly variable according to race, age, and disease state, the cell surface marker CD57 is routinely used to identify terminally differentiated, senescent cells with reduced proliferative capacity and altered functional properties 22 . The expression of CD57 was dramatically elevated in CD4 and CD8 T cells in both patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The expression of CD57 in T cells was also analyzed by flow cytometry 22 . Isolated PBMCs were incubated with anti‐human CD4 (PE‐Cy7), anti‐human CD8 (BV421), and anti‐human CD57 (FITC) for 30 minutes on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, ∼40% of PIK3CD GOF patients also develop clinically relevant autoimmune disease, including autoimmune cytopenias, glomerulonephritis, and autoimmune thyroiditis (Coulter et al, 2017;Lucas et al, 2014;Maccari et al, 2018). Several recent studies have explored the pathogenesis of the immunodeficiency in these patients (Avery et al, 2018;Bier et al, 2019;Cannons et al, 2018;Cura Daball et al, 2018;Edwards et al, 2019;Preite et al, 2018;Preite et al, 2019;Ruiz-García et al, 2018;Stark et al, 2018;Wentink et al, 2017;Wentink et al, 2018;Wray-Dutra et al, 2018). These studies have revealed defects in B cells and CD4 + T cells, thereby elucidating mechanisms for poor antibody responses and susceptibility to respiratory infections, and altered natural killer and CD8 + T cell function, which provide an explanation for the viral susceptibility and possibly malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is produced upon phosphorylation of PIP2 by the phosphoinositide 3-kinases (PI3K), especially PI3Kδ. Interestingly, mutations in the subunits of PI3K also translate into multiple PID associated with decreased NK cell cytotoxicity ( 196 , 197 ) and CD8 + T cell proliferation ( 198 ). In addition to DGK-α, PIP3 also recruits DOCK2, which is needed to drive a Rac1/WAVE2-dependent actin polymerization at the pSMAC ( 199 , 200 ).…”
Section: Genetic Defects Affecting the Formation Stability And Funcmentioning
confidence: 99%